Pengaruh Gaya Kepemimpinan Instruktif, Konsultatif, Partisipatif dan Delegatif terhadap Motivasi Kerja Pada Karyawan CV. Mulia Game Sindo Solo - Arifin, Noor, Dra. Mukaromah, M.M (2015)
The aim of this research is to analyze the influence of leadership style and motivation upon employee performance in the Office of the Secretary, West Sulawesi. The research population consists of all 322 employees of West Sulawesi's Secretary Office. The stratified random sampling technique was employed, along with Slovi's formula, thus the number of employees sampled was 76. The research employed path analysis for testing the hypothesis. The results showed as follows: 1) instruction leadership style directly affects employee performance and influences indirectly through motivation. 2) consultation leadership style directly affects employee performance and influences indirectly through motivation. 3) participation leadership style directly affects employee performance and influences indirectly through motivation and 4) Delegation leadership style directly affects employee performance and influences indirectly through motivation.